Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which, if any, of the given values [tex]\( x = \frac{1}{3} \)[/tex], [tex]\( x = 3 \frac{1}{3} \)[/tex], [tex]\( x = 6 \frac{1}{3} \)[/tex], and [tex]\( x = 9 \frac{1}{3} \)[/tex] are zeros of the quadratic function [tex]\( f(x) = 9x^2 - 54x - 19 \)[/tex], we need to evaluate the function at each of these points and check if the value is zero.
The points to evaluate are:
1. [tex]\( x = \frac{1}{3} \)[/tex]
2. [tex]\( x = 3 \frac{1}{3} \)[/tex]
3. [tex]\( x = 6 \frac{1}{3} \)[/tex]
4. [tex]\( x = 9 \frac{1}{3} \)[/tex]
Let's evaluate the function [tex]\( f(x) \)[/tex] at these points.
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = \frac{1}{3} \)[/tex]:
- Plug [tex]\( x = \frac{1}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{1}{3}\right) = 9\left(\frac{1}{3}\right)^2 - 54\left(\frac{1}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{1}{3}\right) = 9 \cdot \frac{1}{9} - 54 \cdot \frac{1}{3} - 19 = 1 - 18 - 19 = -36 \][/tex]
Hence, [tex]\( f\left(\frac{1}{3}\right) = -36 \)[/tex].
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 3 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{10}{3} \)[/tex].
- Plug [tex]\( x = \frac{10}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{10}{3}\right) = 9\left(\frac{10}{3}\right)^2 - 54\left(\frac{10}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{10}{3}\right) = 9 \cdot \left(\frac{100}{9}\right) - 54 \cdot \left(\frac{10}{3}\right) - 19 = 100 - 180 - 19 = -99 \][/tex]
Hence, [tex]\( f\left(\frac{10}{3}\right) = -99 \)[/tex].
3. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 6 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 6 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{19}{3} \)[/tex].
- Plug [tex]\( x = \frac{19}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{19}{3}\right) = 9\left(\frac{19}{3}\right)^2 - 54\left(\frac{19}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{19}{3}\right) = 9 \cdot \left(\frac{361}{9}\right) - 54 \cdot \left(\frac{19}{3}\right) - 19 = 361 - 342 - 19 \approx 0 \][/tex]
Hence, [tex]\( f\left(\frac{19}{3}\right) \approx 0 \)[/tex].
4. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 9 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 9 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{28}{3} \)[/tex].
- Plug [tex]\( x = \frac{28}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{28}{3}\right) = 9\left(\frac{28}{3}\right)^2 - 54\left(\frac{28}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{28}{3}\right) = 9 \cdot \left(\frac{784}{9}\right) - 54 \cdot \left(\frac{28}{3}\right) - 19 = 784 - 504 - 19 = 261 \][/tex]
Hence, [tex]\( f\left(\frac{28}{3}\right) = 261 \)[/tex].
By evaluating the function [tex]\( f(x) \)[/tex] at these points, we observe that:
- [tex]\( f\left(\frac{1}{3}\right) = -36 \)[/tex]
- [tex]\( f\left(\frac{10}{3}\right) = -99 \)[/tex]
- [tex]\( f\left(\frac{19}{3}\right) \approx 0 \)[/tex]
- [tex]\( f\left(\frac{28}{3}\right) = 261 \)[/tex]
Therefore, the value [tex]\( x = 6 \frac{1}{3} \)[/tex] (or [tex]\( x = \frac{19}{3} \)[/tex]) is a zero of the quadratic function [tex]\( f(x) = 9x^2 - 54x - 19 \)[/tex].
The points to evaluate are:
1. [tex]\( x = \frac{1}{3} \)[/tex]
2. [tex]\( x = 3 \frac{1}{3} \)[/tex]
3. [tex]\( x = 6 \frac{1}{3} \)[/tex]
4. [tex]\( x = 9 \frac{1}{3} \)[/tex]
Let's evaluate the function [tex]\( f(x) \)[/tex] at these points.
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = \frac{1}{3} \)[/tex]:
- Plug [tex]\( x = \frac{1}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{1}{3}\right) = 9\left(\frac{1}{3}\right)^2 - 54\left(\frac{1}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{1}{3}\right) = 9 \cdot \frac{1}{9} - 54 \cdot \frac{1}{3} - 19 = 1 - 18 - 19 = -36 \][/tex]
Hence, [tex]\( f\left(\frac{1}{3}\right) = -36 \)[/tex].
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 3 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{10}{3} \)[/tex].
- Plug [tex]\( x = \frac{10}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{10}{3}\right) = 9\left(\frac{10}{3}\right)^2 - 54\left(\frac{10}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{10}{3}\right) = 9 \cdot \left(\frac{100}{9}\right) - 54 \cdot \left(\frac{10}{3}\right) - 19 = 100 - 180 - 19 = -99 \][/tex]
Hence, [tex]\( f\left(\frac{10}{3}\right) = -99 \)[/tex].
3. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 6 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 6 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{19}{3} \)[/tex].
- Plug [tex]\( x = \frac{19}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{19}{3}\right) = 9\left(\frac{19}{3}\right)^2 - 54\left(\frac{19}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{19}{3}\right) = 9 \cdot \left(\frac{361}{9}\right) - 54 \cdot \left(\frac{19}{3}\right) - 19 = 361 - 342 - 19 \approx 0 \][/tex]
Hence, [tex]\( f\left(\frac{19}{3}\right) \approx 0 \)[/tex].
4. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 9 \frac{1}{3} \)[/tex]:
- Convert [tex]\( x = 9 \frac{1}{3} \)[/tex] to an improper fraction [tex]\( x = \frac{28}{3} \)[/tex].
- Plug [tex]\( x = \frac{28}{3} \)[/tex] into the function:
[tex]\[ f\left(\frac{28}{3}\right) = 9\left(\frac{28}{3}\right)^2 - 54\left(\frac{28}{3}\right) - 19 \][/tex]
- Simplify:
[tex]\[ f\left(\frac{28}{3}\right) = 9 \cdot \left(\frac{784}{9}\right) - 54 \cdot \left(\frac{28}{3}\right) - 19 = 784 - 504 - 19 = 261 \][/tex]
Hence, [tex]\( f\left(\frac{28}{3}\right) = 261 \)[/tex].
By evaluating the function [tex]\( f(x) \)[/tex] at these points, we observe that:
- [tex]\( f\left(\frac{1}{3}\right) = -36 \)[/tex]
- [tex]\( f\left(\frac{10}{3}\right) = -99 \)[/tex]
- [tex]\( f\left(\frac{19}{3}\right) \approx 0 \)[/tex]
- [tex]\( f\left(\frac{28}{3}\right) = 261 \)[/tex]
Therefore, the value [tex]\( x = 6 \frac{1}{3} \)[/tex] (or [tex]\( x = \frac{19}{3} \)[/tex]) is a zero of the quadratic function [tex]\( f(x) = 9x^2 - 54x - 19 \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.